On R1 Space in l-Topological Spaces - Islam, Rafiqul; Hossain, MS (GANIT: Journal of Bangladesh Mathematical Society, 2018)
In this paper, R1 space in L-topological spaces are defined and studied. We give seven definitions of R1 space in L-topological spaces and discuss certain relationship among them. We show that all of these satisfy ‘good extension’ property. Moreover, some of their other properties are obtained. GANIT J. Bangladesh Math. Soc.Vol. 37 (2017) 63-71